P = (\(\dfrac{13}{84}\) x 1\(\dfrac{2}{5}\) - 2\(\dfrac{1}{2}\) x \(\dfrac{7}{180}\)) : 2\(\dfrac{7}{18}\) + 4\(\dfrac{1}{2}\) x \(\dfrac{1}{10}\)
P = (\(\dfrac{13}{84}\) x \(\dfrac{7}{5}\) - \(\dfrac{5}{2}\) x \(\dfrac{7}{180}\)):\(\dfrac{43}{18}\) + \(\dfrac{9}{2}\) x \(\dfrac{1}{10}\)
P = (\(\dfrac{13}{60}\) - \(\dfrac{7}{72}\)): \(\dfrac{43}{18}\) + \(\dfrac{9}{20}\)
P = \(\dfrac{43}{360}\) x \(\dfrac{18}{43}\) + \(\dfrac{9}{20}\)
P = \(\dfrac{1}{20}\) + \(\dfrac{9}{20}\)
P = \(\dfrac{10}{20}\)
P = \(\dfrac{1}{2}\)